The Roles of Virtual Social Networks in Family Cohesion (Case study: Citizens of Tehran) - Talebi, Mohammad; Dehqan, Hossein; Nouroozi, Faizollah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Purpose: The emergence of technology and mass media has affected families, social relations, and its values and has led to changes in the behavior and interactions of family members. As mass media are the most important technologies affecting our world, social networks and the Internet have penetrated in a way that it is impossible to imagine life without them, and they have made positive and negative changes to the family cohesion of users by affecting the form of interactions between people. According to the above topics, the present study aimed to investigate the effect of using virtual social networks on the family cohesion of the citizens of Tehran. Methods: Based on the type of collected and analyzed data, the present research was quantitative, and had a field type in terms of the method of facing with problems. The research technique had a survey. The statistical population was equal to 2915543, the sample size was 375, and the sampling method was a combination of simple and cluster random sampling. The mean use of social networks was 1 hour and 36 minutes per day. Results: The results of the hypothesis test indicated that the hypotheses about the effect of the virtual social networks on intra-family cohesion and its quantitative and qualitative dimensions were confirmed and the effect was direct and positive. The rate of using virtual social networks could predict changes in the family cohesion variable by 9%, the quantitative dimension by 9%, and the qualitative dimension by 27%. Conclusion: The general results indicated that the rate of using social networks caused changes in the level of family cohesion in Tehran users.